Therapeutic Potential of Cannabinoids in Glaucoma - Hit or Myth? - A Review - Julia Górny; Alicja Kapciak; Tomasz Forenc; Jonasz Jurek; Aleksandra Pelczarska; Jaromir Hunia; Marcin Komorowski; Rafał Kaczorowski; Michał Janiszewski (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Glaucoma is a leading cause of irreversible blindness, characterized by elevated intraocular pressure (IOP) that damages the optic nerve. Current treatments mainly focus on reducing IOP, but some patients do not respond adequately to conventional therapies. Cannabinoids, particularly Δ9-tetrahydrocannabinol (Δ9-THC), have been investigated as potential adjunctive treatments for glaucoma. Studies have shown varying effects of cannabinoids on IOP regulation, though their precise mechanisms remain unclear. Aim of Study: This study aims to evaluate the therapeutic potential of cannabinoids in the treatment of glaucoma by examining their effects on IOP, their mechanisms of action, and the risks and benefits associated with their use. Material and methods: A comprehensive literature review of studies on the therapeutic potential of cannabinoids in glaucoma was conducted using the PubMed database. Results and Conclusions: Cannabinoids, especially Δ9-THC, have demonstrated the ability to reduce IOP in both healthy individuals and glaucoma patients. However, the effect is typically short-lived, lasting only 3-4 hours. The efficacy of cannabinoids in reducing IOP is influenced by the method of administration (oral, intravenous, inhalation) and the delivery system used for topical application. Despite some promising results, the use of cannabinoids as a mainstream glaucoma treatment is limited by factors such as the short duration of action, the potential for addiction, and the occurrence of adverse effects like tachycardia, hypotension, and cognitive impairment. Although cannabinoids offer a unique approach to glaucoma management, further research is necessary to address these limitations and determine their long-term therapeutic viability.